IMPACT OF SEWAGE ON WATER QUALITY PROFILE OF SELECTED PONDS OF HUBLI-DHARWAD URBAN ENVIRONMENT, KARNATAKA, INDIA - S. B. KAKKALAMELI; T. C. TARANATH (International Journal of Pharma and Bio Sciences, 2015)
Water resources are being deteriorated day by day at the very faster rate due to the anthropogenic interferences. Such as sewage, industrial waste and domestic waste disposal into the surface water bodies such as lakes and ponds. The present investigation is an attempt to assess the water quality of the selected ponds and sewage channels of the Hubli-Dharwad urban area. The physico-chemical parameters of water on the selected surface water bodies were carried out to prepare the water quality profile. Surface water samples were analyzed for physico-chemical properties such as pH, EC-TDS, Total alkalinity, Hardness , COD, DO and inorganic elements such as Ca, Mg, Cl, Na & K and water quality index (WQI) was calculated. WQI for the selected water bodies ranges between 104.326 to 1855.54 which reveal that the water is of poor quality and is unsuitable for domestic consumption.